Assessing the fermentation quality and microbial community of the mixed silage of forage soybean with crop corn or sorghum. (October 2018) - Ni, Kuikui; Zhao, Jingyun; Zhu, Baoge; Su, Rina; Pan, Yi; Ma, Junkui; Zhou, Guoan; Tao, Yong; Liu, Xiaorong; Zhong, Jin
Graphical abstract: Highlights: Forage soybean ensiled with crop corn or sorghum. Improved forage soybean silage quality was obtained by mixed ensiling. Microbial community in mixed silages differed from forage soybean silage. Lactobacillus was enhanced by mixed ensiling. Abstract: The silage quality of forage soybean (FS) rich in protein with crop corn (CN) or sorghum (SG) rich in water soluble carbohydrate was investigated, and microbial community after ensiling was analyzed. Results showed that pH in mixed silages dropped to 3.5–3.8 lower than 100%FS silage (4.5). Microbial analysis indicated that mixed ensiling could influence the microbial community. Although Lactobacillus and Weissella were the dominant genera in all silage samples, Lactobacillus abundance in mixed silages (33–76%) was higher compared with 100%FS silage (27%). In conclusion, FS ensiled with CN or SG could be an alternative approach to improve FS silage quality.